Fibre wealth - Syed Othman, Sharifah Nabihah; Mohd Tahir, Osman (University Putra Malaysia, 2012)
Empty fruit bunch (EFB) that are considered as waste after the extraction of oil palm fruits can be turned into Fibre Wealth. The EFBs need to be shredded, separated, refined and dried. Characteristically EFB fibres are clean, biodegradable, compatible than many other fibres from other wood species and the high quality oil palm fibre are non-toxic since there are no chemicals involved in the production of oil palm fibre. The fibre length, moisture content, oil content and impurities are the critical characteristics of oil palm fibre. After the process, the product of high quality oil palm fibre can be used by manufacturers to become various fibre composites used in furnitures, infrastructures, mattresses, erosion control, paper production and landscaping. The choice and selection of fibre length is very much dependent on the nature of the manufactured product. For example, long fibre length is suitable for mattresses and short fibres make excellent particle board.